A Ca(2+)/CaM-regulated transcriptional switch modulates stomatal development in response to water deficit - Yoo, Chan Yul (Sci Rep, 2019)
Calcium (Ca(2+)) signals are decoded by the Ca(2+)-sensor protein calmodulin (CaM) and are transduced to Ca(2+)/CaM-binding transcription factors to directly regulate gene expression necessary for acclimation responses in plants. The molecular mechanisms of Ca(2+)/CaM signal transduction processes and their functional significance remains enigmatic. Here we report a novel Ca(2+)/CaM signal transduction mechanism that allosterically regulates DNA-binding activity of GT2-LIKE 1 (GTL1), a transrepressor of STOMATAL DENSITY AND DISTRIBUTION 1 (SDD1), to repress stomatal development in response to water stress. We demonstrated that Ca(2+)/CaM interaction with the 2(nd) helix of the GTL1 N-terminal trihelix DNA-binding domain (GTL1N) destabilizes a hydrophobic core of GTL1N and allosterically inhibits 3(rd) helix docking to the SDD1 promoter, leading to osmotic stress-induced Ca(2+)/CaM-dependent activation (de-repression) of SDD1 expression. This resulted in GTL1-dependent repression of stomatal development in response to water-deficit stress. Together, our results demonstrate that a Ca(2+)/CaM-regulated transcriptional switch on a trihelix transrepressor directly transduces osmotic stress to repress stomatal development to improve plant water-use efficiency as an acclimation response.